Etika dan Estetika Sebagai Pedoman Nilai Profesionalisme Konselor - Amirah, Nadiratul; Karneli, Yeni; Handayani, Puji Gusri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The professionalism of a counselor is not only determined by the mastery of technical knowledge and skills, but is also supported by ethical and aesthetic values that are the foundation in the practice of guidance and counseling services. Counselor ethics include a commitment to moral principles such as integrity, responsibility and confidentiality. While aesthetics refer to sensitivity to the beauty of harmonious, empathetic and dignified human relations. This article aims to examine the role of ethics and aesthetics in shaping the professionalism of counselors and how these values are applied in real practice. Through a qualitative descriptive approach and literature study, this article finds that ethics provides a normative framework for a counselor, while aesthetics enrich the quality of the counseling relationship by creating a humane and meaningful experience. Ethical and aesthetic integrity are essential in building trust and the success of counseling services.